Revisiting the immune landscape post spinal cord injury: More than black and white - Zhen-Gang, Liu; Fan, Yang; Jingwei, Shi; Pengyu, Chang; Shengman, Yu; Bo-Yin, Zhang (Frontiers in Aging Neuroscience, 2022)
Spinal cord injury (SCI) induced catastrophic neurological disability is currently incurable, especially for elderly patients. Due to the limited axon regeneration capacity and hostile microenvironment in the lesion site, essential neural network reconstruction remains challenging. Due to the blood-spinal cord barrier (BSCB) created immune cells and cytokines isolation, the immune elements were incorrectly recognized as innocent bystanders during the SCI pathological process traditionally. Emerging evidence demonstrated that the Central nervous system (CNS) is an “immunological quiescent” rather than “immune privileged” area, and the CNS-associated immune response played essential and mixed roles throughout the crucial SCI recovery stages. Among these roles, immune response dedicates beneficial and detrimental contributions throughout the SCI process. Consequently, coordinating double-edged immunomodulation is vital to tissue repair and neurological recovery. The comprehensive exploration and understanding of the immune landscape post SCI are essential in establishing new avenues for further basic and clinical studies. In this context, this review summarizes the recent significant breakthroughs in CNS immunomodulation discovery. Moreover, the currently existing immune-oriented therapies for SCI will be outlined.